Comparative effects of Salvizan gel (containing Salvia officinalis extract) and triamcinolone acetonide gel on the duration and symptoms of oral lichenoid reactions - Parichehr Ghalayani; Fahimeh Pakravan; Fatemeh Abbasi (University Library System, University of Pittsburgh, 2022)
Objectives: Lichenoid reactions are disorders with similar clinical presentations. The current study was conducted to compare the improvement indices in the patients' symptoms by Salvizan and triamcinolone gels. Therefore, regardless of the cause, eliminating the pain and symptoms is one of the objectives of the treatment. Methods: This study was designed as a randomized double-blind clinical trial. Diagnosis of patients was performed by clinical examinations and confirmed by histological evaluation. One group of patients was administered Salvizan and another group was administered triamcinolone. After washing their mouth, the patients administered the gel (1 cm) on the inflammatory mucosa three times a day for two weeks. The amelioration rate of the lesions in each visit was measured from according to Visual Analog Scale (VAS) on a scale of 0-10. Results: The results of repeated measures ANCOVA showed a significant difference between groups in terms of the pain intensity before treatment (p<0.001). Moreover, there was a significant difference between different times with regard to pain intensity (p=0.004). To evaluate the clinical indices in the study groups, Mann-Whitney test was used and the results showed no significant difference for the extent of lesions before treatment (p=0.874), after one week (p=0.503) and after two weeks (p=0.669). Conclusions: Salvizan could better reduce pain intensity than triamcinolone, but clinically no significant difference was reported between the drugs in terms of the extent of lesion.